Applying the cognitive congruence principle to target language training - Sergey A. Volkov (Peoples' Friendship University of Russia (RUDN University), 2023)
Though the cognitive congruence principle has been studied and used in education, the problem of designing technologies for its integration and functioning, particularly in target language training, remains open. In training within the learning process, i.e., exploring learned material rather than introducing it, educators may think congruence tutoring will fit as a tool for applying this principle. By developing a cognitive congruence-performing model, the study aims to objectivise cognitive congruence, i.e., involve aligning learning goals with learning experience processing, student abilities or learning styles with instructional design, and tutoring with tuteeing and delivering to the educational cluster. Here, the question arises of why and how the cognitive congruence principle can reconfigure the learning experience. The process-oriented method establishes the importance of dynamics, cooperation, and transformation as well as teaching, tutoring, and tuteeing processes to produce the cognitive congruence model performance. It refers to methodological triangulation within the method that covers the exploratory data analysis: process tracing, process screening, and process evaluation. The model and instructions as congruence research application results in facilitating knowledge, imparting and enhancing the cognitive experience in students' chosen field; ensuring alignment with the educational milieu, procedure, content, and outcomes and integrating teaching and learning strategies; giving new momentum to decision-making skills via increasing collective thinking and streamline complex problem-solving, cultural acceptance, social responsibility, and self-assessment. The frame-alignment entity establishes a workable and eligible integral pattern for discussion and creative use. Education congruence is adaptable to practical guidelines for planning and implementing enrichment training and learning systems in intercultural and interdisciplinary communication teach-in environments.